Replication data for: "Application of thermography for monitoring stomatal conductance of Coffea arabica under different shading systems" - Craparo, Alessandro Carmelo William; Steppe, K.; Asten, Piet J.A. van; Läderach, Peter R.D.; Jassogne, Laurence T.P.; Grab, S.W. (International Center for Tropical Agriculture, 2018)
The primary objective of the data collection was to analyse the relationship between leaf temperatures and stomatal conductance. Data were collected under both environmentally controlled (laboratory) conditions as well as field conditions. Major variables studied and produced include thermographic indices derived from temperature measurements and stomatal conductance indices derived from a leaf porometer.